Assessing the Relation between Personality Traits with Intention to Whistleblowing - Minoo Afshani; Hojat Vahdati; Mohammad Hakak; Sayed Najomdin Moosavi (Tehran University of Medical Sciences, 2018)
Background: Whistleblowing as a control tool should be encouraged in organizations to deter organizational illegal and immoral wrongdoings that finally are harmful to the society. Personality traits of people are influential factors on their intention to disclose the wrongdoings. This study aimed to assess the relationship between four personality traits (internal locus of control, ethical identity, extroversion and responsibility) and employeeschr('39') intention to whistleblowing among the employees of central department of Mashhad University of Medical Sciences. Materials and Methods: This cross-sectional study is a descriptive-analytic one. This research conducted on 251 employees of the central department of Mashhad University of Medical Sciences. A researcher-made questionnaire based on previous literature used to collect the data. Analysis of the data processed using the Partial Least Square (PLS) with Smart PLS software.  Results: Since, the amount of standardized coefficients between independent variables (locus of control, ethical identity, extroversion and responsibility) and whistleblowing intention were statistically significant (P<0.005), all of these independent variables have positive and significant influence on the employeeschr('39') whistleblowing intention. Conclusion: Given that individuals with internal locus of control, ethical identity, responsibility and extroversion characteristics cannot be able to ignore the organizational wrongdoings, it is better organizations use employees with these characteristics at more sensitive or critical places, where the possibility of organizational wrongdoing is high, in order to prevent potential harm to the organization and society as a result of wrongdoings.